Effect of two amendments on seedling growth of two cashew varieties - Castellanos Gonzalez, Leonides; Tabaco Puerta, Raúl Adolfo; Castellanos Hernández, Leónides (Revista de Ciencias Agrícolas, 2024)
Cashew, Anacardium occidentale L., is considered a promising crop for many regions in Colombia, requiring further research on new varieties and technologies. This study aimed to evaluate the effect of two organic amendments on two cashew varieties under nursery conditions in Puerto Carreño, Vichada department. A factorial experiment (3 organic amendment treatments x 2 varieties) with 4 replications was conducted. The treatments for the first factor were: chicken manure (30%), bovine manure (30%), and no amendment. The varieties used were Yucao and Mapiria. Emergence, survival, and morphometric variables such as stem length, stem diameter, and number of leaves were evaluated, as well as disease incidence and severity. Results showed that seedling emergence and survival were more influenced by the addition of organic amendments than by varieties. Stem length of cashew seedlings was influenced by the addition of bovine and chicken manure and their interaction with the two varieties until week 7, while stem diameter was influenced until the end of the nursery cycle. Neither variety nor treatment influenced the number of leaves. Anthracnose was primarily influenced by the variety factor, with Mapiria being more susceptible to both disease incidence and severity. Overall, both organic amendments had a significant effect on the development of cashew seedlings in both varieties studied.